2019
DOI: 10.3390/md17050271
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Rare Homo-Amino Acid Containing Variants of Microcystin by a Benthic Cyanobacterium

Abstract: Microcystins are a family of chemically diverse hepatotoxins produced by distantly related cyanobacteria and are potent inhibitors of eukaryotic protein phosphatases 1 and 2A. Here we provide evidence for the biosynthesis of rare variants of microcystin that contain a selection of homo-amino acids by the benthic cyanobacterium Phormidium sp. LP904c. This strain produces at least 16 microcystin chemical variants many of which contain homophenylalanine or homotyrosine. We retrieved the complete 54.2 kb microcyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
1
16
1
Order By: Relevance
“…Therefore, strains that do not produce MCs can result from inactivation either by point mutation, or by partial or complete deletion of mcy genes [36,57,59,60]. Recently, Shishido et al [61] reported that the mcy gene cluster did not encode all enzymes for the synthesis of rare variants of MC that contain a selection of homo-amino acids by the benthic cyanobacterium Phormidium sp. LP904c, but may instead activate homo-amino acids produced during the synthesis of anabaenopeptins.…”
Section: Biosynthesis Of Microcystinsmentioning
confidence: 99%
“…Therefore, strains that do not produce MCs can result from inactivation either by point mutation, or by partial or complete deletion of mcy genes [36,57,59,60]. Recently, Shishido et al [61] reported that the mcy gene cluster did not encode all enzymes for the synthesis of rare variants of MC that contain a selection of homo-amino acids by the benthic cyanobacterium Phormidium sp. LP904c, but may instead activate homo-amino acids produced during the synthesis of anabaenopeptins.…”
Section: Biosynthesis Of Microcystinsmentioning
confidence: 99%
“…While production of Mdha 7 were reported for Planktothrix agardhii NIVA CYA 126/8 [12], Microcystis aeruginosa NIES 843 and Fischerella sp. CENA161 [3,6], Dha 7 was the only AA residue reported for M. aeruginosa K-139 [12]. Among the investigated species in this study, Mdhb 7 formation was only reported for Nostoc sp.…”
Section: Resultsmentioning
confidence: 87%
“…Among the investigated species in this study, Mdhb 7 formation was only reported for Nostoc sp. 152 [27] that also produced Dha 7 , MeSer 7 and Mdha 7 [12,25] containing MCs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Presently, PKS and non-ribosomal peptide synthase (NRPS) are in the spotlight. In cyanobacteria, PKS has been known to synthesize toxic compounds such as microcystin ( Shishido et al, 2019 ) and swinholide ( Humisto et al, 2018 ). In some marine bacteria, PKS synthesize very long chain fatty acids, such as docosahexaenoic acids ( Okuyama et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%